2022
DOI: 10.1088/1748-3190/ac6374
|View full text |Cite
|
Sign up to set email alerts
|

Propulsion optimization of a jellyfish-inspired robot based on a nonintrusive reduced-order model with proper orthogonal decomposition

Abstract: In this research, the propulsion of the proposed jellyfish-inspired mantle undulated propulsion robot (MUPRo) is optimized. To reliably predict the hydrodynamic forces acting on the robot, the proposed non-intrusive reduced-order model (NIROM) based on proper orthogonal decomposition (POD) additionally considers the POD basis that has an important contribution to the features on the specified boundary. The proposed model establishes a mapping between the parameter-driven motion of the mantle and the evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…Studies have revealed that the size of a computational domain affects the solution accuracy of unsteady problems [57][58][59]. Based on this, the size of the computational domain is strictly consistent with the size used in the 2D prototype experiments (figure 1(C)), the details can be find in the recent work [29]. As shown in figure 1(B), the size of the 2D numerical pool is 2000 mm × 500 mm, the mantle starts at (500 mm, 120 mm), and the front of the main cabin is located at (300 mm, 0).…”
Section: Geometric Assumption and High Fidelity Modellingsupporting
confidence: 76%
See 4 more Smart Citations
“…Studies have revealed that the size of a computational domain affects the solution accuracy of unsteady problems [57][58][59]. Based on this, the size of the computational domain is strictly consistent with the size used in the 2D prototype experiments (figure 1(C)), the details can be find in the recent work [29]. As shown in figure 1(B), the size of the 2D numerical pool is 2000 mm × 500 mm, the mantle starts at (500 mm, 120 mm), and the front of the main cabin is located at (300 mm, 0).…”
Section: Geometric Assumption and High Fidelity Modellingsupporting
confidence: 76%
“…Moreover, we applied axisymmetric assumptions in the HF model and the subsequent ROM to reduce the number of elements required for the simulation to converge, since both the computational domain and the undulating motion of the mantle are symmetric about the x-axis. However, it is worth mentioning that the lofting result for the 2D computational domain, where the rotational symmetry assumption is applied, does not entirely agree with the 3D prototype due to the neglect of the connection between the mantle and the main cabin [29].…”
Section: Geometric Assumption and High Fidelity Modellingmentioning
confidence: 92%
See 3 more Smart Citations